2021
DOI: 10.1155/2021/5776487
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Influence of High-Dose rhGH Therapy on Serum Vitamin D and IGF-1 Levels in School-Age Children with Idiopathic Short Stature

Abstract: Objective. To discuss the influence of high-dose recombinant human growth hormone (rhGH) therapy on serum vitamin D and insulin-like growth factor-1 (IGF-1) levels in school-age children with idiopathic short stature (ISS). Method. A total of 103 school-age children with ISS were selected from June 2016 to June 2020 in our hospital. The enrolled cases were divided into the low-dose group (n = 59) and high-dose group (n = 44) according to the treatment dose of rhGH. After the treatment, the height (Ht), height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Припускається, що 25-гідроксилювання вітаміну D відбувається у мітохондріях та мікросомах печінки і в цьому процесі бере участь фермент цитохрому Р-450. ГР може посилювати активність P-450 мітохондрій печінки за допомогою прямої або непрямої дії ІФР-1, викликаючи тим самим активацію вітаміну D [18]. ГР може посилювати активність ниркової 1α-гідроксилази, тим самим викликаючи активацію вітаміну D та підвищення його рівня у сироватці.…”
Section: таблиця 1 аналіз деяких показників сироватки крові у дітей з...unclassified
“…Припускається, що 25-гідроксилювання вітаміну D відбувається у мітохондріях та мікросомах печінки і в цьому процесі бере участь фермент цитохрому Р-450. ГР може посилювати активність P-450 мітохондрій печінки за допомогою прямої або непрямої дії ІФР-1, викликаючи тим самим активацію вітаміну D [18]. ГР може посилювати активність ниркової 1α-гідроксилази, тим самим викликаючи активацію вітаміну D та підвищення його рівня у сироватці.…”
Section: таблиця 1 аналіз деяких показників сироватки крові у дітей з...unclassified
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%